Climate as a risk factor for tourism - Németh, Ákos; Mika, János (Acta Geographica Debrecina Landscape & Environment series, 2009)
Weather and climate risk factors for tourism are surveyed and illustrated with regard to the expected climate changes in Hungary. These changes are not at all advantageous and which affect the business in question both directly and indirectly. These are the summer resort tourism (characterised by bioclimatic indices). Green tourism is the next one to characterise, including skiing, mountain climbing and eco-tourism, as well. Here both day-to-day weather extremes and long-lasting effects on the biota (e.g. drought, or inundation for plain-area eco-tourism). Last, but not least the urban (cultural- and shopping-) tourism is presented, since the large towns exhibit their special climate and different risks. The paper intends to specify these meteorological factors and effects also in terms of the different types of touristic activities. The general statements on the effect of weather and climate on tourism are illustrated by a few individual parameters and also by the so called Physiologically Equivalent Temperature. Annual and diurnal course of this parameter are presented, together with various trends in this variable at different sites and in different (hot and cold) extremities of the occurring values. Other examples, helping the tourism industry are presented in various climate conditions of the country. They include high precipitation and high relative humidity information. The paper also lists the possible adaptation measures to extreme events and also their likely changes in time.